2020
DOI: 10.3168/jds.2019-16710
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray ionization mass spectrometry characterization of ubiquitous minor lipids and oligosaccharides in milk of the camel (Camelus dromedarius) and their inhibition of oxidative stress in human plasma

Abstract: The aim of this study was to characterize minor lipids in methanol fraction extracted from raw camel milk after loading it on a water-preconditioned short C18 open column and fractionating with a gradient of methanol/water. The C18 column showed high fractionation efficiency of minor lipids, such as glycosphingolipids, lipopolysaccharides, or oligosaccharides, when compared with other constituents, in particular polysaccharides, proteins, and free fatty acids. Liquid chromatography electrospray ionization tand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
(83 reference statements)
1
1
0
Order By: Relevance
“…Moreover, the content of 8-amino-7-oxononanoate and chloramphenicol palmitate increased 123 and 53 times. The significantly increased chloramphenicol palmitate demonstrated better probiotic function, which has been the same effect as chloramphenicol and can treat inflammation, which was consistent with previous studies that camel milk has antibacterial and anti-inflammatory effects [ 3 ]. There was no research on the use of thiram and many other esters in camel milk, and there is currently a lack of research on the toxicological or pharmacological effects of these substances.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, the content of 8-amino-7-oxononanoate and chloramphenicol palmitate increased 123 and 53 times. The significantly increased chloramphenicol palmitate demonstrated better probiotic function, which has been the same effect as chloramphenicol and can treat inflammation, which was consistent with previous studies that camel milk has antibacterial and anti-inflammatory effects [ 3 ]. There was no research on the use of thiram and many other esters in camel milk, and there is currently a lack of research on the toxicological or pharmacological effects of these substances.…”
Section: Discussionsupporting
confidence: 89%
“…A report by Muleta et al demonstrated that camel milk intervention can reduce the incidence of anaemia in children in Somalia and eastern Ethiopia [ 2 ]. Additionally, camel milk is rich in phytochemicals with anti-cancer, anti-platelet and anti-thrombotic properties, and is beneficial in the treatment of chronic hepatitis and the improvement of liver function [ 3 , 4 ]. For instance, Korish and coworkers have demonstrated that full fat cow milk and camel milk have hypoglycemic and anticoagulant effects on diabetic rats induced by streptozotocin [ 5 ].…”
Section: Introductionmentioning
confidence: 99%